Study on nucleotide, myofibrillar protein biochemical properties and microstructure of freeze-dried scallop striated muscle during storage and rehydration - Wei, Huamao; Golam Rasul, Md; Sun, Zhongqi; Yang, Wenge; Huang, Tao; Yamashita, Tetsuro; Takaki, Koichi; Yuan, Chunhong (Food research international, 2022)
[Display omitted] •The ATP content of dried scallops kept unchanged during storage at room temperature.•ATP decomposed rapidly during rehydration.•Ca2+-ATPase activity of dried scallop kept unchanged during rehydration process.•Rod of myosin was not stable during rehydration resulted in low salt solubility. The biochemical properties and microstructural changes of freeze-dried Japanese scallop (Patinopecten yessoensis) striated muscle during room temperature storage and rehydration were investigated. The results showed that the content of ATP in freeze-dried scallop muscle remained stable with no significant difference (p > 0.05). However, ATP was rapidly decomposed and AMP accumulated within 1.5 min of rehydration, and HxR and Hx were gradually produced from AMP decomposition with the extension of rehydration time. Besides, the results of chymotryptic digestion patterns demonstrated that the rod of myosin was unstable after dehydration, reflecting lower salt solubility than that of frozen-thawed scallop. In contrast, the myosin subfragment-1 (S-1) was stable, as indicated by the constant of Ca2+-ATPase activity of freeze-dried scallops throughout the storage and rehydration (p > 0.05). Furthermore, the microstructural analysis revealed that the Z line of the freeze-dried scallop was broken after dehydration process. This study might be useful for developing high-quality dehydrated scallops in the future.